2018
DOI: 10.1111/ejh.13109
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying immature platelets as markers of increased platelet production after coronary artery bypass grafting surgery

Abstract: Of the 3 markers, IPC was the most promising as surrogates for platelet production. Future studies should evaluate the utility of the IPC to identify patients with cardiovascular disease with reduced response to aspirin who might benefit from twice-daily aspirin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…The trajectory of platelet count is shown in Fig. 3D and its pattern is similar to previous researches [16,22,23]. During CPB, the platelets were severely diluted and damaged and about 80% of patients required platelet transfusion to control bleeding from the suturing properly.…”
Section: Coagulation System Risk Factorssupporting
confidence: 79%
“…The trajectory of platelet count is shown in Fig. 3D and its pattern is similar to previous researches [16,22,23]. During CPB, the platelets were severely diluted and damaged and about 80% of patients required platelet transfusion to control bleeding from the suturing properly.…”
Section: Coagulation System Risk Factorssupporting
confidence: 79%
“…Several potential explanations have been proposed for the nature of high on-treatment platelet reactivity, including modifiable factors: too low doses of anti-platelet drugs, high platelet turnover, oxidative stress, dyslipidaemia and inflammation [7][8][9][10][11][12]. Coronary artery bypass grafting surgery itself is associated with excessive activation of platelets, which results in stimulation of the production and release of young platelets [2,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research also observed this phenomenon and argued that this process is indicative of a persistent platelet activation and aggregation in the first three postoperative days. [16,22,23] In the present study, the platelet count delayed to show the rising tendency in the conventional group because those patients experienced a larger quantity of blood loss from the chest tube in the first 3 preoperative days. There were 69.2% of patients in the ABO group and 82.6% in the conventional group (P = 0.003) whose last re-examination of platelet count during in hospital stay was higher than the preoperative level (platelet rebound).…”
Section: Coagulation System Risk Factorsmentioning
confidence: 46%
“…The trajectory of platelet count is shown in Figure 3D and its pattern is similar to previous researches. [16,22,23] During CPB, the platelets were severely diluted and damaged and about 80% of patients required platelet transfusion to control bleeding from the suturing properly. Even with the plasma and platelet transfusion, the bleeding from the chest tube was still relatively large in the earlier postoperative days [Table and Supplementary Figure 1].…”
Section: Coagulation System Risk Factorsmentioning
confidence: 99%